Synthesis and Characterization of Peptide-Chitosan Conjugates (PepChis) with Lipid Bilayer Affinity and Antibacterial Activity - Petrin, Thais H. Costa; Fadel, Valmir [UNESP]; Martins, Danubia B. [UNESP]; Dias, Susana A.; Cruz, Ana; Sergio, Luciana Marciano; Arcisio-Miranda, Manoel; Castanho, Miguel A. R. B.; Dos Santos Cabrera, Marcia P. [UNESP] (American Chemical Society (ACS), 2019)
Antimicrobial peptides appear among innovative biopolymers with potential therapeutic interest. Nevertheless, issues concerning efficiency, production costs, and toxicity persist. Herein, we show that conjugation of peptides with chitosans can represent an alternative in the search for these needs. To increase solubility, deacetylated and degraded chitosans were prepared. Then, they were functionalized via N-succinimidyl-S-acetylthiopropionate or via glutathione (GSH), an endogenous peptide linker. To the best of our knowledge, it is the first time that GSH is used as a thiolating agent for the conjugation of peptides. Next, thiolated chitosans were conjugated through a disulfide bond with designed short-chain peptides, one of them derived from the antimicrobial peptide Jelleine-I. Conjugates and respective reaction intermediates were characterized by absorciometry, attenuated total reflectance-Fourier transform infrared, and 1H NMR. Zeta potential measurements showed the cationic nature of these biomacromolecules and their preferential partitioning to Gram-positive bacterial-like model membranes. In vitro investigation using representative Gram-positive and -negative bacteria (Staphylococcus aureus and Escherichia coli, respectively) showed that the conjugation strategies lead to enhanced activity in relation to the unconjugated peptide and to the unconjugated chitosan. The obtained products showed selectivity toward S. aureus at low cytotoxicity as determined in NIH/3T3 cells. Overall, our study demonstrates that an appropriate choice of antimicrobial peptide and chitosan characteristics leads to increased antimicrobial activity of the conjugated product and represents a strategy to modulate the activity and selectivity of antimicrobials resorting to low-cost chemicals. The present proposal starts from less expensive raw materials (chitosan and short-chain peptide), is based on aqueous solvents, and minimizes the use of reactants with a higher environmental impact. The final biopolymer contains the backbone of chitosan, just 3-6% peptide derived from royal jelly and GSH, all of them considered safe for human use or as a physiological molecule.